The very busy spider - Carle, Eric. (New York : Philomel, 1989)
The farm animals try to divert a busy little spider from spinning her web, but she persists and produces a thing of both beauty and usefulness. The pictures may be felt as well as seen.
K-3.
K-3
Keywords: Toy and movable books -- Specimens; Domestic animals -- Fiction; Spider webs -- Fiction; Spiders -- Fiction; Toy and movable books; Domestic animals -- Fiction; Spiders -- Fiction; Toy and movable books